2018
DOI: 10.1159/000486830
|View full text |Cite
|
Sign up to set email alerts
|

An Arabic Version of the Geriatric Depression Scale (30 Items): Psychometric Properties and Some Findings in a Lebanese Elderly Sample

Abstract: Background/Aim: Although the rates of depression and anxiety disorders have been shown to be higher in older people, especially those living in institutional settings, most of this population remains undiagnosed and untreated. The objective is to translate the full-scale Geriatric Depression Scale (30 items, GDS) into Arabic for use in elderly patients in Lebanon, to check its validity and reproducibility in comparison to the original version of the questionnaire, and assess the risk factors associated with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…19−26 Depressive symptoms are also common within sub-populations of older adults, reaching a prevalence of 46% in those with Parkinson's disease 27 and 57% to 86% in dementia of Alzheimer's type and vascular dementia, respectively. 28 Most studies identified living alone, 22−25 living in a nursing home, 25,29,30 illiteracy, 25,29,30 and having chronic diseases 19,24,25 to be associated with geriatric depression.…”
Section: Status Of Geriatric Mental Health In the Arabmentioning
confidence: 99%
“…19−26 Depressive symptoms are also common within sub-populations of older adults, reaching a prevalence of 46% in those with Parkinson's disease 27 and 57% to 86% in dementia of Alzheimer's type and vascular dementia, respectively. 28 Most studies identified living alone, 22−25 living in a nursing home, 25,29,30 illiteracy, 25,29,30 and having chronic diseases 19,24,25 to be associated with geriatric depression.…”
Section: Status Of Geriatric Mental Health In the Arabmentioning
confidence: 99%
“…Vivir en un hogar de ancianos, el estrés, la ansiedad, estar casado, la edad y el nivel educativo primario aumentarían significativamente la depresión (β = 2.211, β = 0.223, β = 0.041, β = 0.902, β = 0.118 y β = 3.533, respectivamente). Un estado nutricional normal y un nivel educativo universitario disminuirían significativamente la depresión (β = -0,732; β = -1,961) (Hallit et al, 2018). Por lo contrario, en Turquía al reclutar un total de 329 pacientes adultos mayores ambulatorios.…”
Section: Discussionunclassified
“…Another study in 2018 22 conducted to evaluate the psychometric properties of the Arabic version of 30-item GDS showed a positive significant relationship between all items of this scale and the main scale. Cronbach's alpha coefficient was 0.90 indicating a high internal consistency for the scale.…”
Section: Discussionmentioning
confidence: 99%